Formação de profissionais da educação e o curso de Pedagogia - Nogueira, Maria do Carmo de Oliveira (2001)
The general objective of the present study was to analyze how the course of Pedagogy of UNIPAR has contributed to the formation of teachers. It was tried to answer the following questions: How the course of Pedagogy has contributed to the formation o teachers? Which is the historical trajectory of curricular organization of the Course of Pedagogy in the ambit of Brazilian education and in the context of UNIPAR? What think the teachers and students about the curricular organization of the Course of Pedagogy of UNIPAR - Campus Umuarama - Headquarters? What are the points of advance and the points which difficult the curricular organization of the Course of Pedagogy? For the development of the study it was opted for qualitative research which objectifíed to apprehend the reality in focus of its uncertainty, in its multidimensionality, of formation and to extract a greater number of analysis. It was tried to indicate among other aspects, by means of structured interviews to teachers and questionnaire to students registered in the years of 2000 and 2001 in the Paranaense University UNIPAR - Campus Umuarama -Headquarters, ways which can orientate the reformulation of the Course of Pedagogy in the Paranaense University UNIPAR. It was concluded that teachers and students consider curricular organization of the Course of Pedagogy as significant to professional formation. The description which teachers and students the university made about developed practices in the course induced to the idea that innovations lead by them are based in an epistemological conception different than traditional. They reveal, in their speeches a perception of knowledge that is found present as in the content taught as, mainly, in how it is taught. The knowledge extends here beyond information, as ways of thinking, seeing, feeling and acting in the world. The fundamental questions of this investigation orientated, in its theoretical-methodological purpose, to the supposition that there is a process of rupture of traditional paradigms in the daily pedagogic practice in the university in study. Understanding the process of teaching as a revelation of movements and discoveries, it is also concluded, that context and subjects of research are in a constant interaction and in permanent change. The fíndings here described suggest to integrate accumulated knowledge about the thematic and, somehow, to contribute to the collective effort that has been done in the area of didactic and formation of teachers, which better contribute to the qualification of these fields of acting.